Theme structure in an introduction section of articles published in Indonesian national journals - T. Thyrhaya Zein; T. Silvana Sinar; Nurlela Nurlela; Tasnim Lubis; Rusdi Noor Rosa (Universitas Syiah Kuala, 2023)
One of the important parts of a research article is an introduction. As the initial part of an article, it should provide all the ideas confirming that the study needs to be conducted. Therefore, the ideas presented should be well organized. One of the ways to confirm a good organization of ideas in the introduction is by paying attention to the theme structure used to build the clauses. This study analyzed the theme types and structure used in the introduction section of articles published in Indonesian national journals. This study was conducted using qualitative content analysis. Using a documentation technique, the data were collected from 15 research articles published in the latest volumes (2020-2021) of four Indonesian national journals. The data were analyzed using a content analysis method, following the established procedure of the clause theme analysis. The results of the study found the dominant use of simple themes in the introduction section of the research articles, indicating a lack of ideas organization. Besides, it was also found that the theme structure of the clauses was realized in nine theme patterns. These patterns are used in presenting different contents of an introduction. It is concluded that theme types and patterns contribute to producing a good quality introduction section of a research article.